Split of spatial attention as predicted by a systems-level model of visual attention - Zirnsak, Marc; Beuth, Frederik; Hamker, Fred H. (The European journal of neuroscience, 2011)
Can we attend to multiple distinct spatial locations at the same time? According to a recent psychophysical study [J. Dubois et al. (2009)Journal of Vision, 9, 3.1–11] such a split of spatial attention might be limited to short periods of time. Following N. P. Bichot et al. [(1999)Perception & Psychophysics, 61, 403–423] subjects had to report the identity of multiple letters that were briefly presented at different locations, while two of these locations (targets) were relevant for a concurrent shape comparison task. In addition to the design used by Bichot et al. stimulus onset asynchrony between shape onset and letters was systematically varied. In general, the performance of subjects was superior at target locations. Furthermore, for short stimulus onset asynchronies, performance was simultaneously increasing at both target locations. For longer stimulus onset asynchronies, however, performance deteriorated at one of the target locations while increasing at the other target location. It was hypothesized that this dynamic deployment of attention might be caused by competitive processes in saccade‐related structures such as the frontal eye field. Here we simulated the task of Dubois et al. using a systems‐level model of attention. Our results are consistent with recent findings in the frontal eye field obtained during covert visual search, and they support the view of a transient deployment of spatial attention to multiple stimuli in the early epoch of target selection.